TRANSFORMASI PEMBELAJARAN BERBASIS DIGITAL DALAM PENDIDIKAN AKUNTANSI - Putra Umar Sakka, Gjosphink; Ramly, Ramly; Juwantho Lewa, Muhammad; Muh. Syata, Wahyu; Arfan, Muhammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Digital transformation in accounting education plays a crucial role in enhancing the learning experience through technologies such as Learning Management Systems (LMS), cloud-based simulations, and artificial intelligence (AI). The use of LMS platforms like Moodle has been shown to improve material distribution and interaction between instructors and students, while cloud-based simulations allow students to practice accounting directly in a virtual environment. However, key challenges in implementing digital learning include the digital divide, infrastructure limitations, and the lack of training and pedagogical readiness of educators. This study employs a narrative literature review approach to examine 25 articles published between 2015 and 2025, with the aim of exploring trends, challenges, and the potential of technology adoption in accounting education. The main findings indicate that while digital learning can enhance students' technical skills, the success of technology implementation heavily relies on educators' readiness and adequate infrastructure support. This study recommends developing a curriculum that is more adaptable to technological advancements and industry needs, as well as enhancing training for educators to maximize the benefits of digital learning in accounting education. ABSTRAK Transformasi digital dalam pendidikan akuntansi memainkan peran penting dalam meningkatkan pengalaman belajar melalui teknologi seperti Sistem Manajemen Pembelajaran (LMS), simulasi berbasis cloud, dan kecerdasan buatan (AI). Penggunaan LMS seperti Moodle telah terbukti meningkatkan distribusi materi dan interaksi antara pengajar dan siswa, sementara simulasi berbasis cloud memungkinkan mahasiswa untuk berlatih akuntansi secara langsung dalam lingkungan virtual. Meskipun demikian, tantangan utama yang dihadapi dalam implementasi pembelajaran digital meliputi kesenjangan digital, keterbatasan infrastruktur, serta kurangnya pelatihan dan kesiapan pedagogis dari pendidik. Penelitian ini menggunakan pendekatan tinjauan literatur naratif untuk mengkaji 25 artikel yang diterbitkan antara tahun 2015 hingga 2025, dengan tujuan untuk mengeksplorasi tren, tantangan, dan potensi penerapan teknologi dalam pendidikan akuntansi. Temuan utama menunjukkan bahwa meskipun pembelajaran digital dapat meningkatkan keterampilan teknis mahasiswa, kesuksesan implementasi teknologi sangat bergantung pada kesiapan pengajar dan dukungan infrastruktur yang memadai. Penelitian ini merekomendasikan pengembangan kurikulum yang lebih adaptif terhadap perkembangan teknologi dan kebutuhan industri, serta peningkatan pelatihan bagi pendidik untuk memaksimalkan manfaat pembelajaran digital dalam pendidikan akuntansi